Reduction of Uroporphyrinogen Decarboxylase by Antisense RNA Expression Affects Activities of Other Enzymes Involved in Tetrapyrrole Biosynthesis and Leads to Light-Dependent Necrosis. - Mock, H. P. (1997)
We introduced a full-length cDNA sequence encoding tobacco (Nicotiana tabacum) uroporphyrinogen III decarboxylase (UROD; EC 4.1.1.37) in reverse orientation under the control of a cauliflower mosaic virus 35S promoter derivative into the tobacco genome to study the effects of deregulated UROD expression on tetrapyrrole biosynthesis. Transformants with reduced UROD activity were characterized by stunted plant growth and necrotic leaf lesions. Antisense RNA expression caused reduced UROD protein levels and reduced activity to 45% of wild type, which was correlated with the accumulation of uroporphyrin(ogen) and with the intensity of necrotic damage. Chlorophyll levels were only slightly reduced (up to 15%), indicating that the plants sustained cellular damage from accumulating photosensitive porphyrins rather than from chlorophyll deficiency. A 16-h light/8-h dark regime at high-light intensity stimulates the formation of leaf necrosis compared with a low-light or a 6-h high-light treatment. Transgenic plants grown at high light also showed inactivation of 5-aminolevulinate dehydratase and porphobilinogen deaminase, whereas the activity of coproporphyrinogen oxidase and the 5-aminolevulinate synthesizing capacity were not altered. We conclude that photooxidation of accumulating uroporphyrin(ogen) leads to the generation of oxygen species, which destabilizes other enzymes in the porphyrin metabolic pathway. This porphyrin-induced necrosis resembles the induction of cell death observed during pathogenesis and air pollution.